Multielectrode Pulmonary Vein Isolation Versus Single Tip Wide Area Catheter Ablation for Paroxysmal Atrial Fibrillation: A Multinational Multicenter Randomized Clinical Trial. (April 2016) - Boersma, Lucas V.; van der Voort, Pepijn; Debruyne, Pilippe; Dekker, Lukas; Simmers, Tim; Rossenbacker, Tom; Balt, Jippe; Wijffels, Maurits; Degreef, Yves
Abstract : Background—: Single-shot ablation techniques may facilitate safe and simple pulmonary vein isolation to treat paroxysmal atrial fibrillation. Multielectrode pulmonary vein isolation versus single tip wide area catheter ablation-paroxysmal atrial fibrillation is the first multinational, multicenter, prospective, noninferiority randomized clinical trial comparing multielectrode-phased radiofrequency ablation (MEA) to standard focal irrigated radiofrequency ablation (STA) using 3-dimensional navigation. Methods and Results—: Patients with paroxysmal atrial fibrillation were randomized to MEA (61 patients) or STA (59 patients). Preprocedure transesophageal echocardiogram and computed tomography/magnetic resonance imaging (also 6-month postprocedure) were performed. Mean age was 57 years, 25% female sex, BMI was 28, CHA2 DS2 –VASc score was 0 to 1 in 82%, 8% had previous right atrial ablation, whereas all had at least 1 antiarrhythmic drug failure. The MEA group had significantly shorter mean procedure time (96±36 versus 166±46 minutes, P <0.001) and fluoroscopy time (23±9 versus 27±9 minutes, P =0.023). The total radiofrequency energy duration was 22±8 minutes for MEA versus 36±13 minutes for STA ( P <0.001) with confirmed pulmonary vein isolation in all patients. Hospital admission was 1 day in both groups, without major adverse events either during the procedure or during 30-day follow-up. Two patients in the STA group had 1 PV with asymptomatic narrowing >50%. Freedom of atrial fibrillation for MEA and STA was 86.4% and 89.7% at 6 months, dropping to 76.3% and 81.0% at 12 months. Conclusions—: In this multicenter, randomized clinical trial, MEA and STA had similar rates of single-procedure acute pulmonary vein isolation without serious adverse events in the first 30 days. MEA had slightly lower long-term arrhythmia freedom, but showed marked and significantly shorter procedure, fluoroscopy, and radiofrequency energy times. Clinical Trial Registration—: URL:www.clinicaltrials.gov ; Unique identifier: NCT01696136.